1987
DOI: 10.1177/002199838702100901
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Highly Filled Magnetic Polymeric Composites

Abstract: The mechanical properties of ferrite filled thermoplastics at high filler loadings of 75-85% by weight are reported. Barium ferrite was used as the filler in the magnetic polymeric composites. Three types of thermoplastic elastomers, namely, styrenic, polyester-ether, and polyurethane were investigated as matrix materials. Low density polyethylene was also studied as a non-elastomeric reference matrix. The dependence of the strength at break, elongation and modulus on the matrix type, filler amount and strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, theoretically there are other factors that might influence tensile properties such as shape of particles, filler dispersion and filler-matrix adhesion. [24][25][26][27][28] The shape of the filler particle also may affect the properties of the composites. It is reported that spherical filler reinforced composite has higher tensile strength while the composite reinforced with irregular filler showed lower tensile strength.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…However, theoretically there are other factors that might influence tensile properties such as shape of particles, filler dispersion and filler-matrix adhesion. [24][25][26][27][28] The shape of the filler particle also may affect the properties of the composites. It is reported that spherical filler reinforced composite has higher tensile strength while the composite reinforced with irregular filler showed lower tensile strength.…”
Section: Tensile Propertiesmentioning
confidence: 99%